The wavelength dependence of the photoplethysmogram and its implication to pulse oximetry - Damianou., Damianos. (1995)
Since the early 1980s the increase in use of pulse oximeters in many clinical situations has been quite remarkable, turning it into one of the most important methods of monitoring in use today. Pulse oximetry essentially uses photoplethysmography to calculate oxygen saturation. Consequently the wavelength dependence of the photoplethysmogram (PPG) is of direct relevance in the performance of pulse oximeters.